(untitled) (Bangladesh Medical Journal Khulna, 2017)
Background: Early pregnancy failure is a major health problem across the globe. This is particularly important for the woman of Bangladesh. Objective: The aim of our study was to evaluate the safety and efficacy of manual vacuum aspiration (MVA) compared to dilatation and curettage (D&C) in the management of first trimester abortion. Methods: This was a prospective randomised study done in Obstetrics & Gynaecology department of Jessore medical college & Khulna medical college. Over a period of one year from January 2014 to December 2014, a total of four hundred women presented with spontaneous miscarriage with gestational age < 12 weeks patients with no sign of septic abortion and no history of pregancy with fibroid uterus were included in the study. Results: These patients underwent random selection either MVA group (n = 200) or D&C group (n=200). Cases were compared with respect to age, parity, gestational age, risk, blood loss, time taken & complications. The distribution of age, parity & gestational age was similar in both groups. The mean duration of procedure was significantly higher (P<.0001) in D&C group compared to MVA group. The duration of hospital stay was significantly lower (P<.0001) in MVA group compared to D&C group. Similarly the cost of the procedure was significantly lower (P<.0001) in MVA group compared to D&C group. Conclusion: MVA is safe, effective, cheaper, less time consuming and requires shorter hospital stay. It does not require general anaesthesia and complication is also less than dilation and curettage. So it can be easily accessible to the woman of both rural and urban societies belonging to any socioeconomic strata specially where high tech equipments and power supply are not available. Bang Med J (Khulna) 2016; 49 : 18-22